Socioeconomic Determinants of Agricultural Extension Needs among Yam Farmers in Nasarawa State, Nigeria - Danlami Haruna Yakubu; Gumugumu Godknows Brakiebou Douseifa; Ango Adamu Kamba; Jazuli Alhassan (Journal of Agricultural Extension, 2025)
This study assessed the socioeconomic determinants of agricultural extension needs among yam farmers in Nasarawa State, Nigeria. A multistage sampling procedure involving both purposive and random selection was used to select 295 farmers for the study. Data were obtained with the aid of a questionnaire and analyzed using percentages and Multiple Linear Regression Model. Findings of the study revealed that the major extension needs of the farmers included information on time of planting (90.17%), spacing of tubers (98.64%), pests and diseases control (94.58%), how to source for credit (96.95%) and method of weed control (95.25%). The study also found that sex, education, extension contact, and access to credit were significantly and positively related to agricultural extension needs of the yam farmers. Additionally, age, farm size, and annual income were all significantly related to agricultural extension needs of the farmers. The study recommends targeting extension services to specific groups of yam farmers based on their socioeconomic characteristics, providing training and education on recommended yam production practices, and improving access to credit facilities.